Force-velocity profile of competitive kayakers: Evaluation of a novel single kayak stroke test - Petrovic, M.; García-Ramos, A.; Janicijevic, D.; Pérez-Castilla, A.; Knezevic, O. M.; Mirkov, D. M. (Journal of Human Kinetics, 2021)
The assessment of the force-velocity (F-V) profile in athletes may have im portant applications for training prescription, injury management, and fatigue monitoring. This study aimed to assess whether a novel single kayak stroke test (SKST) is able to provide the F-V relationship variables (maximum force, maximum velocity and maximum power) of competitive kayakers with acceptable reliability and external validity. Six female (age: 20.3 ± 3.7 years) and eight male (age: 20.8 ± 2.4 years) elite kayakers performed the SKST, bench press, bench pull, and short Wingate kayak test. The individual F-V relationships were highly linear [median r (range): left stroke = 0.986 (0.897 - 0.998); right stroke = 0.987 (0.971 - 0.999)]. The reliability of the F-V relationship parameters obtained during the SKST was high (within-session: CV = 4.48% and ICC = 0.93; between-session: CV = 8.06% and ICC = 0.65). The validity of the F-V relationship parameters obtained during the SKST was generally very high for maximum power (r range = 0.825 - 0.975), high for maximum force during both the bench press and the bench pull (r range = 0.751 - 0.831), and high or moderate for maximal velocity during the bench pull (r = 0.770 - 0.829) and the bench press (r = 0.355 - 0.471), respectively. The SKST can be considered a feasible procedure for testing the maximal upper-body muscle mechanical capacities of kayakers.